Effective car-buying approaches for younger Chinese buyers: a systematic literature review synthesis on customer personality, emotion, and behavior in automotive purchasing - Chen, Jiandou; Ibrahim, Rahinah; Azmi, Athira (Academia Industry Networks, 2023)
Younger consumers have taken a major position in the automobile market in China as they are taking the lead in driving the national vehicle consumption. Despite having lower financial capacity, young customers are driven by the emotional pride to “show off” their acquired ownership. In lieu of this, this paper is proposing to give young customers a luxurious experiential perception while they continue buying affordable cars which will boost the sales of domestic automobiles. This paper is a desktop survey attempting to understand through a systematic literature review synthesis process on recent findings about customer’s personality, emotion, and behavior in order to highlight the trends, fill in gaps and suggest approaches for reaching out to younger Chinese auto buyers. Results of this study lead towards proposing a personalized carbuying approach that utilizes technology to customize the in-car ambience and respects customer privacy will improve the car-buying experience and increase customer satisfaction. Future studies are recommended to enhance the car user experience among young Chinese buyers.